(untitled) (Fiep Bulletin - online, 2011)
The intestinal parasitosis or endoparasitosis, associated with protozoa and / or helminthes, represent a serious problem of public health, particularly in the underdeveloped countries, where they are highly disseminated and prevalent due to the poor life conditions of the more lacking population layers. The most important factors that influence this situation are: absent or deficient environmental sanitation, inadequate hygiene practices and precarious conditions where millions of people live. The objective of this work was to identify and to treat endoparasitosis in third age patients. The study was of a longitudinal and analytical type with quantitative and descriptive approach. The participants’ selection occurred in the Municipal Service of Health (MSH) in Campina Grande-PB and the exams were made in the Parasitology Laboratory of the Biological Sciences Center of Health of the Universidad Estatal de Paraíba (UEPB), in the period of March to August of 2007. The results were collected in Excel (2003) software and Epi-info 3.5.1 for Windows and described in absolute and percentile numbers. Of the 107 participants, 32% had parasites. Most were women among 60 - 69 years, they had a monthly income of 1-2 minimum wages, were retired and beneficiary through the services of garbage collection and the net of channeled water. The detected endoparasitosis were: monoparasitism with to E. histolytica and the S. stercoralis; biparasitism with E. histolytica/E.coli and E. nana/A.lumbricoides and in the multiple parasitism, E. histolytica/E. coli/G. lamblia. The pharmacotherapy for helmintiasis was accomplished through the Albendazol 400mg and the Metronidazol 250mg in the cases of protozoa. Studies of this type should be accomplished frequently to contribute with the improvement in the quality of the elderly life, which in Brazil and the world are presenting an increase in the longevity, demanding new ways of caring from the health professionals.